Hemodynamic shear stress stimulates migration and extravasation of tumor cells by elevating cellular oxidative level. (1st March 2017) - Ma, Shijun; Fu, Afu; Chiew, Geraldine Giap Ying; Luo, Kathy Qian
Abstract: Cancer cells are shed into the blood stream and are exposed to hemodynamic shear stress during metastasis. It has been shown that shear stress can destroy circulating tumor cells (CTCs) both in vitro and in vivo . However, it remains unclear whether shear stress can modulate the properties and functions of tumor cells in a manner that might help CTCs to exit circulation. In this study, we established a microfluidic circulatory system to apply physiological fluid shear stress on breast cancer cells and demonstrated that an arterial level of shear stress significantly enhanced tumor cell migration in transwell and wound healing assays, and enhanced extravasation in a transendothelial assay. Circulatory treatment elevated the intracellular levels of reactive oxygen species (ROS), which is an early and indispensable event for activating the extracellular signal-regulated kinases (ERK1/2). Subsequently, ERK1/2 activation promoted the migration of tumor cells and enhanced their extravasation. Finally, reducing cellular ROS production suppressed tumor cell extravasation in both a transendothelial assay and a zebrafish model. This new understanding of how fluid shear stress promotes tumor cell migration has important implications in cancer treatment and can help us to identify potential therapeutic targets for inhibiting tumor progression. Highlights: This is the first report on the pro-metastatic effect of shear stress on tumor cells. Fluid shear stress promotes the migration and extravasation of tumor cells. Fluid shear stress confers this effect by generating ROS which then activates ERK1/2. Antioxidants suppress the migration and extravasation of tumor cells in zebrafish model.